Commercial Vegetable Production: Pumpkins - Marr, Charles W.; Schaplowsky, Terry; Carey, Ted (My University, 2004)
This publication describes how to produce pumpkins commercially in Kansas.
MF2030_2004_11
Keywords: MF2030; Crops; fruits and vegetables; Lawn and Garden; MF